Autism spectrum disorders in infants and toddlers : diagnosis, assessment, and treatment - 4 0 16; Chawarska, Katarzyna,;Klin, Ami,;Volkmar, Fred R.; 5 (New York : The Guilford Press, 2008)
Examines the methods used to diagnose and treat infants and toddlers with autism spectrum disorders, explaining why it is so important to recognize the signs and get a diagnosis as early as possible and highlighting critical research issues and assessment tools.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Mental health.;Mental health.;diagnosis.;therapy. -- Autism in children.;Infants;Toddlers;Autistic Disorder;Autistic Disorder;Child.;Infant.;Autism.; 20; 2